2020
DOI: 10.1002/cbdv.202000758
|View full text |Cite
|
Sign up to set email alerts
|

New Isoflavones with Antioxidant Activity Isolated from Cornulaca monacantha

Abstract: In the course of phytochemical and chemotaxonomical investigations of Cornulaca monacantha (Amaranthaceae), two new isoflavones, 3-(2-hydroxyphenyl)-5,7-dimethoxy-6-(methoxymethyl)-4H-1-benzopyran-4-one (1) and 7-hydroxy-3-(4-hydroxyphenyl)-5-methoxy-6-(methoxymethyl)-4H-1-benzopyran-4-one (2) were isolated from the fresh aerial parts of C. monacantha among with three known compounds named vanillic acid (3), N-cisferuloyltyramine (4) and N-trans-feruloyltyramine (5). Their structures were elucidated by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The percentages of inhibition were calculated using the following formula: PI% ¼ ½ðAbs blank -Abs sample Þ=Abs blank � � 100 Total antioxidant capacity was determined according to previous method. [15,43] For this assay gallic acid was used as a positive control.3 mL of reagent solution were added to 0.3 mL of extract (0.6 M sulfuric acid, 28 mM sodium phosphate and 4 mM ammonium molybdate). The mixture was placed in a boiling water bath for 90 min; the absorbance was determined at a wavelength of 734 nm.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of inhibition were calculated using the following formula: PI% ¼ ½ðAbs blank -Abs sample Þ=Abs blank � � 100 Total antioxidant capacity was determined according to previous method. [15,43] For this assay gallic acid was used as a positive control.3 mL of reagent solution were added to 0.3 mL of extract (0.6 M sulfuric acid, 28 mM sodium phosphate and 4 mM ammonium molybdate). The mixture was placed in a boiling water bath for 90 min; the absorbance was determined at a wavelength of 734 nm.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…Antioxidants do not all have the same mode of action, consequently, antioxidant potency must be assessed using multiple methods. [15] In the present research work, the isolates from T. tartonraira were subjected to an in vitro antioxidant activity evaluation using three methods, namely DPPH, Ferric Reducing Antioxidant Power (FRAP) and Total Antioxidant Capacity (TAC) assays. The DPPH assay was conducted to evaluate the ability of the compounds to reduce DPPH * free radical (2,2-diphenyl-1-picrylhydrazyl).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…monacantha Del. is an annual herb growing wild in Egypt, in Arabic known as "Had" and is commonly known as "had and djouri" (Mhiri et al, 2020). The current systematic classification of C. monacantha is listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Decoction of the leaves is used in folk medicine for treatment of jaundice, also considered as an excellent pasture for camels, especially for its effect on milk production as well as its beneficial purgative effect. It has spiny leaves which used to treat scabies (Mhiri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro antioxidant and antimicrobial activities of the three extracts were also evaluated. It has been demonstrated that more than one method is necessary to elucidate the antioxidant capacity of samples because these assays differ in the principal and experimental conditions [ 10 , 11 ]. Thus, we used four different complementary antioxidant assays (FRAP, TAC, DPPH, and ABTS) and compared to that of commercial antioxidants such as vitamin C and Trolox.…”
Section: Introductionmentioning
confidence: 99%